GPER1 Silencing Suppresses the Proliferation, Migration, and Invasion of Gastric Cancer Cells by Inhibiting PI3K/AKT–Mediated EMT - Xu, En; Xia, Xuefeng; Jiang, Chaoyu; Li, Zijian; Yang, Zhi; Zheng, Chang; Wang, Xingzhou; Du, Shangce; Miao, Ji; Wang, Feng; Wang, Yizhou; Lu, Xiaofeng; et al. (Frontiers in Cell and Developmental Biology, 2020)
G protein coupled estrogen receptor (GPER1) is a membrane estrogen receptor, belonging to the seven-transmembrane G protein-coupled receptors family, and has important biological functions in cancer. However, the functional role of GPER1 in gastric cancer (GC) remain incompletely understood. In the present study, we employed gene set enrichment analysis and discovered that GPER1 expression was concomitant with EMT process and was positively correlated with activation of the PI3K/AKT pathway in GC. Knockdown of GPER1 with siRNA suppressed the proliferation, migration, and invasion of AGS and MGC-803 GC cells. Knockdown of GPER1 also downregulated the mesenchymal markers N-cadherin and vimentin, upregulated E-cadherin, an epithelial marker, and suppressed expression of the Snail, Slug and Twist1 transcription factors, indicating that knockdown of GPER1 inhibited EMT. Moreover, 740Y-P, a PI3K activator, reversed the effects of GPER1 knockdown on EMT processes. Overexpression of GPER1 with plasmid can further prove these findings. In summary, these data demonstrate that GPER1 inhibition suppresses the proliferation, migration, and invasion of gastric cancer cells by inhibiting PI3K/AKT-mediated EMT. Our study elucidated the function of GPER1 in gastric cancer, and we identified PI3K/AKT-mediated EMT as a novel mechanism by which GPER1 contributes to proliferation, migration, and invasion of gastric cancer. These data suggest that combining inhibition of GPER1 and PI3K may be a potential therapeutic approach to inhibit gastric cancer metastasis.